(z-7)(z+3)=-24

Simple and best practice solution for (z-7)(z+3)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (z-7)(z+3)=-24 equation:


Simplifying
(z + -7)(z + 3) = -24

Reorder the terms:
(-7 + z)(z + 3) = -24

Reorder the terms:
(-7 + z)(3 + z) = -24

Multiply (-7 + z) * (3 + z)
(-7(3 + z) + z(3 + z)) = -24
((3 * -7 + z * -7) + z(3 + z)) = -24
((-21 + -7z) + z(3 + z)) = -24
(-21 + -7z + (3 * z + z * z)) = -24
(-21 + -7z + (3z + z2)) = -24

Combine like terms: -7z + 3z = -4z
(-21 + -4z + z2) = -24

Solving
-21 + -4z + z2 = -24

Solving for variable 'z'.

Reorder the terms:
-21 + 24 + -4z + z2 = -24 + 24

Combine like terms: -21 + 24 = 3
3 + -4z + z2 = -24 + 24

Combine like terms: -24 + 24 = 0
3 + -4z + z2 = 0

Factor a trinomial.
(1 + -1z)(3 + -1z) = 0

Subproblem 1

Set the factor '(1 + -1z)' equal to zero and attempt to solve: Simplifying 1 + -1z = 0 Solving 1 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1z = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1z = 0 + -1 -1z = 0 + -1 Combine like terms: 0 + -1 = -1 -1z = -1 Divide each side by '-1'. z = 1 Simplifying z = 1

Subproblem 2

Set the factor '(3 + -1z)' equal to zero and attempt to solve: Simplifying 3 + -1z = 0 Solving 3 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1z = 0 + -3 -1z = 0 + -3 Combine like terms: 0 + -3 = -3 -1z = -3 Divide each side by '-1'. z = 3 Simplifying z = 3

Solution

z = {1, 3}

See similar equations:

| 2x^3+11x^2-67x-36=0 | | (5x+4)-(-8x)= | | 4x+y+2x+y= | | D=4n+na | | 5x-0y=14 | | 5m^2=-35m+40 | | 12y^2+49y+30= | | p/-5=-2/5 | | (2x-2)+(x+1)+x+(x+1)=x+(2x-9)+(x+1)+(x+8)+x | | P=4L+3w | | 10(z-4)=(12)z/2 | | 9pq^4-9pr^4=0 | | 2h^2-11h-40= | | 3x/6x^3 | | -(4x-2y-2)= | | 0=8d^2-26d-15 | | 2(m+4)-3m=14 | | (X+8)=29 | | log[5](2x^6)=0 | | z/5-5=7/6 | | -50=-6x-5(-2x+18) | | x/12-3=11/24 | | 8+3x=2x-9 | | 2x^3+21x^2=40x | | 180=x+6.2x | | 3x+8=2y+x | | 6x-x=-2-3 | | 16+1x=-5x+8 | | .5x+2=-3y | | y=8+12 | | 2-3/10=10 | | 25p^2-70p+49=0 |

Equations solver categories